Systematic review of EASY-care needs assessment for community-dwelling older people - Craig, Chris; Chadborn, Neil; Sands, Gina; Tuomainen, Helena; Gladman, John R.F. (Oxford University Press, 2015)
Background: undertaking comprehensive geriatric assessments (CGAs) combined with long-term health and social care management can improve the quality of life of older people [ 1]. The EASY-Care tool is a CGA instrument designed for assessing the physical, mental and social functioning and unmet health and social needs of older people in community settings or primary care. It has also been used as a frailty assessment tool and for gathering population-level data.